Debt crises and sovereign risk in Africa - Mathebula, Ndzalama (Routledge, 2025)
"This book examines the resurgence of debt crises in Africa following the Covid-19 pandemic. It deciphers the debt crisis phenomenon through the discourse of sovereign risk, which has been paid insufficient attention within the African context. It seeks to appreciate facets that continue to lead African states to a debt-default position. The book focuses on the pre-stages of default and debt default risks. It explores and investigates whether South Africa was and continues to be financially capable of servicing its International Monetary Fund (IMF) loan, granted in 2020 for the COVID-19 pandemic. While investigating how and why Ethiopia and Ghana have already defaulted on their post-pandemic loans from the IMF. It examines the idea of sovereign risk in Africa through a qualitative methodology and a case study research design, analyzing three countries borrowed from the IMF in 2020 or later, mainly prompted by the pandemic. The book distinguishes between African states that have not yet defaulted and those that have already defaulted on their debt servicing. Namely, South Africa, Ethiopia, and Ghana, two of which have already defaulted on their loan. The book also notes the resurgence of the IMF within the African continent while assessing the past narrative and impact of the international monetary system and how it has changed in the post-pandemic era. However, economic diversification has been noted as a prominent remedy that holds the potential of strengthening African economies and aiding their eradication of the debt crisis. The book is designed to appeal to numerous reading communities, namely scholars, researchers, advanced students and policymakers"-- Provided by publisher.
Keywords: International Monetary Fund -- Africa, Sub-Saharan.; Debts, Public -- Africa, Sub-Saharan.; Debts, External -- Africa, Sub-Saharan.; elektronické knihy; electronic books